2013
DOI: 10.1002/cam4.96
|View full text |Cite
|
Sign up to set email alerts
|

Hormone profiling, WHO 2010 grading, and AJCC/UICC staging in pancreatic neuroendocrine tumor behavior

Abstract: Pancreatic neuroendocrine tumors (pNETs) are the second most common pancreatic neoplasms, exhibiting a complex spectrum of clinical behaviors. To examine the clinico-pathological characteristics associated with long-term prognosis we reviewed 119 patients with pNETs treated in a tertiary referral center using the WHO 2010 grading and the American Joint Committee on Cancer/International Union Against Cancer (AJCC/UICC) staging systems, with a median follow-up of 38 months. Tumor size, immunohistochemistry (IHC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 20 publications
2
23
1
Order By: Relevance
“…The observed mean age of PNEN patients, 59.4 years, was slightly higher than in other studies (48-53 years), possibly due to having an adult group, in contrast with the presence of adolescent patients in other studies that showed an age range of 14-78 years [34,41,42]. Although in this study, women accounted for 75.0% of patients, PNEN incidence is considered equal in both sexes.…”
Section: Clinical Datacontrasting
confidence: 85%
See 2 more Smart Citations
“…The observed mean age of PNEN patients, 59.4 years, was slightly higher than in other studies (48-53 years), possibly due to having an adult group, in contrast with the presence of adolescent patients in other studies that showed an age range of 14-78 years [34,41,42]. Although in this study, women accounted for 75.0% of patients, PNEN incidence is considered equal in both sexes.…”
Section: Clinical Datacontrasting
confidence: 85%
“…PNENs are associated with significantly better outcomes than is pancreatic ductal adenocarcinoma (PDAC). The median survival of surgically treated non-functional PNENs was 60.4 months and the mean survival of PNEN patients reached 225.3 months [34,35]. In contrast, the median survival of surgically treated PDAC was 22.8 months [36].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Insulinoma constitutes approximately 25% of all pancreatic neuroendocrine tumors (PNETs), which represent only 1-2% of all pancreatic neoplasms [3,4]. Clinical diagnosis of insulinoma often takes a long time because of the numerous effects of hypoglycemia and the difficulty of localization, especially when the tumors are small.…”
Section: Discussionmentioning
confidence: 99%
“…While NAFLD is associated with metabolic risk factors such as obesity, diabetes, and dyslipidemia, its etiology remains largely unknown and the development or co-existence of NAFLD in patients with insulinoma has not been investigated [1][2][3][4]. Here we report a case of insulinoma with NAFLD, in which surgical resection of the tumor drastically improved NAFLD-related parameters and hypoglycemia.…”
mentioning
confidence: 88%